Musculoskeletal Radiology Teaching at a UK Medical School: Do We Need to Improve?. Issue 3 (5th November 2018) - Marino, Katherine; Merrick, Deborah; Edwards, Kimberly; Pratten, Margaret
Abstract : The United Kingdom is currently facing crisis due to a shortage of radiology consultants despite ever‐increasing demand for medical imaging. The specifics of how best to teach radiology has generated increasing interest. This study aims to determine whether musculoskeletal (MSK) radiology teaching at the University of Nottingham (UoN) Medical School is perceived to be satisfactory by medical students, Foundation‐Year doctors, and senior medical professionals in preparing students for the demands working as Foundation‐Year doctors. Questionnaires were distributed to all medical students and Foundation‐Year doctors that graduated from UoN ( n = 307). Semi‐structured interviews were conducted with consultants and teaching staff ( n = 13). Forty‐nine percent of preclinical medical students, 43% of clinical students and 27% of Foundation‐Year doctors thought MSK radiology teaching was not sufficient in preparing them for the radiology challenges Foundation‐Year doctors' face. This difference was statistically significant ( P < 0.001). The consensus from senior medical professionals was that MSK Radiology teaching is currently adequate and producing competent students. Interestingly, only 5% of students were considering a career in radiology compared to 34% of Foundation‐Year doctors. Overall, there seems to be concern among students regarding MSK radiology teaching and students have a lack of confidence with MSK radiology. Foundation‐Year doctors and senior medical professionals do not share this view. This may be due to medical students' lack of clarity on what is required of them. Formal documentation of set learning objectives for MSK radiology throughout the curriculum may address this.